Proteasome Biology Is Compromised in White Matter After Asphyxic Cardiac Arrest in Neonatal Piglets. Issue 20 (16th October 2018) - Santos, Polan T.; O'Brien, Caitlin E.; Chen, May W.; Hopkins, C. Danielle; Adams, Shawn; Kulikowicz, Ewa; Singh, Rashmi; Koehler, Raymond C.; Martin, Lee J.; Lee, Jennifer K.
Abstract : Background: Neurological deficits in hypoxic‐ischemic encephalopathy, even with therapeutic hypothermia, are partially attributed to white matter injury. We theorized that proteasome insufficiency contributes to white matter injury. Methods and Results: Neonatal piglets received hypoxia‐ischemia (HI) or sham procedure with normothermia, hypothermia, or hypothermia+rewarming. Some received a proteasome activator drug (oleuropein) or white matter–targeted, virus‐mediated proteasome knockdown. We measured myelin oligodendrocyte glycoprotein, proteasome subunit 20S (P20S), proteasome activity, and carbonylated and ubiquitinated protein levels in white matter and cerebral cortex. HI reduced myelin oligodendrocyte glycoprotein levels regardless of temperature, and myelin oligodendrocyte glycoprotein loss was associated with increased ubiquitinated and carbonylated protein levels. Ubiquitinated and carbonyl‐damaged proteins increased in white matter 29 hours after HI during hypothermia to exceed levels at 6 to 20 hours. In cortex, ubiquitinated proteins decreased. Ubiquitinated and carbonylated protein accumulation coincided with lower P20S levels in white matter; P20S levels also decreased in cerebral cortex. However, proteasome activity in white matter lagged behind that in cortex 29 hours after HI during hypothermia. Systemic oleuropein enhanced white matter P20S and protected the myelin, whereas proteasome knockdown exacerbated myelin oligodendrocyte glycoprotein loss and ubiquitinated protein accumulation after HI. At the cellular level, temperature and HI interactively affected macroglial P20S enrichment in subcortical white matter. Rewarming alone increased macroglial P20S immunoreactivity, but this increase was blocked by HI. Conclusions: Oxidized and ubiquitinated proteins accumulate with HI‐induced white matter injury. Proteasome insufficiency may drive this injury. Hypothermia did not prevent myelin damage, protect the proteasome, or preserve oxidized and ubiquitinated protein clearance after HI.